A study on drag reduction scheme of 200MW DACCU bag filter. Issue 1 (March 2020) - Lyu, Yu kun; Yang, Jiaxi; Wang, Jiawen
Abstract: The DACCU bag filter is the main equipment of pollution control in power plant. The resistance is closely related to its structure. Based on the original structure size and field measured operation parameters of bag filter, the CFD was used for numerical simulation analysis to find out the area with the largest resistance in the original model, thereby meeting the actual demand of the overall resistance reduction and flue gas uniform distribution of the bag filter. Accordingly, three successive improvement schemes were designed from three aspects of flue gas inflow derection, flue gas distribution plate's angle and the number of distribution plates. The numerical simulation method was used to optimize to the minimum resistance to ensure the safe and stable operation of the unit. It provides a reference for relevant engineering design.